Direktinvestitionsströme deuten die Deindustrialisierung Deutschlands an - Christian Rusche (Wirtschaftsdienst, 2025)
– The direct investment flows of Germany since 2018 are remarkable in the context of long-term development and global direct investment activities. While inflows to Germany have been below average in recent years, outflows from Germany - with the exception of 2024 - have been above average. These investments are increasingly flowing to the USA, despite recent unfavourable exchange rate developments. Conversely, investments in Germany remain scarce despite favourable exchange rates. Given that Germany's structural crisis likely began as early as 2018, the signs are growing that a relocation of companies and deindustrialisation are taking place.
Keywords: E22; F21; G11; 330; Auslandsinvestition; Internationaler Wettbewerb; Deindustrialisierung; Deutschland; Auslandsinvestition; Internationaler Wettbewerb; Deindustrialisierung; Deutschland